904 'Excuse me, Sir?' - A Case for Compassion and Non-discrimination in Surgery. (12th October 2021) - Murray, J; Mitchell, P
Abstract: Background: The delivery of compassionate and non-discriminatory care to all patients in the hospital environment is vital. Yet, this striking surgical case report demonstrates that ignorance and prejudice against transgender patients still exists, resulting in poorer health outcomes. Case presentation: A 64-year-old transgender woman presented with severe epigastric pain and left arm weakness. She became haemodynamically unstable as a result of Type A aortic dissection during thrombolysis for a presumed ischaemic stroke. The patient was addressed as 'Sir' on multiple occasions causing her visible distress; she confided in the team that she felt judged and that her concerns were not taken seriously. When the thoracic surgery registrar was informed that the patient was transgender and used female pronouns, their reply was that this information was 'irrelevant' and 'unimportant'. Conclusions: Barriers to health care for transgender individuals and a focus on compassion when treating the surgical patient are discussed. A lack of education, individual ignorance and the serious nature of this case led to psychological distress and may have contributed to a delay in diagnosis. There is an urgent need to raise awareness of transgender health disparities in medical and surgical training, to ensure that all patients are treated equally, and their dignity is maintained, even in challenging and stressful situations. Appropriate engagement and leadership from senior members of the surgical team will foster non-discriminatory practices and the creation of an inclusive environment, focusing on the use of correct pronouns and addressing patient concerns.